2018
DOI: 10.1101/269795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endoglycosidase S enables a highly simplified clinical chemistry assay procedure for direct assessment of serum IgG undergalactosylation in chronic inflammatory disease

Abstract: Over the past 30 years, it has been firmly established that a wide spectrum of (autoimmune) diseases such as rheumatoid arthritis, Crohn’s and lupus, but also other pathologies like alcoholic and non-alcoholic steatohepatitis (ASH and NASH) are driven by chronic inflammation and are hallmarked by a reduced level of serum IgG galactosylation. IgG (under)galactosylation is a promising biomarker to assess disease severity, and monitor and adjust therapy. However, this biomarker has not been implemented in routine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…113 Liver disease is an attractive field for the study of the serum glycome because most N-glycans found in whole serum are attached to serum proteins produced in the liver 21 and to a lesser extent to Igs, 20,70,114 which are produced by B cells. Alterations in serum glycan structures have been reported in patients with liver diseases 20,22,90,92,114,115,116 (Figure 4). Some glycomic-based markers have potential for clinical use (Figures 3, 5, and 6).…”
Section: Diagnostic and Prognostic Markers Of Liver Diseasementioning
confidence: 95%
“…113 Liver disease is an attractive field for the study of the serum glycome because most N-glycans found in whole serum are attached to serum proteins produced in the liver 21 and to a lesser extent to Igs, 20,70,114 which are produced by B cells. Alterations in serum glycan structures have been reported in patients with liver diseases 20,22,90,92,114,115,116 (Figure 4). Some glycomic-based markers have potential for clinical use (Figures 3, 5, and 6).…”
Section: Diagnostic and Prognostic Markers Of Liver Diseasementioning
confidence: 95%
“…2,4 EndoS has been investigated in numerous applications: as a therapy for antibody-mediated autoimmune diseases, such as systemic lupus erythematosus, epidermolysis bullosa acquisita, and idiopathic thrombocytopenia purpua; 5−8 as an enhancer of monoclonal antibody therapy; 9 as a tool for the chemoenzymatic synthesis of antibodies with homogeneous glycosylation or drug conjugates; 10−12 and as a method to screen for chronic inflammatory disease states. 13 Another Streptococcus pyogenes antibody-disrupting enzyme, IdeS, cleaves antibodies in their hinge region, and has shown promise in clinical trials for reducing antibody-mediated organ transplant rejection, revealing yet another possible application for endoglycosidases. 14 It was recently discovered that Streptococcus pyogenes serogroup M49 secretes a unique endoglycosidase, EndoS2, which may offer several potential therapeutic and biotechnological advantages compared to EndoS.…”
Section: ■ Introductionmentioning
confidence: 99%